Prioritizing the protection and creation of natural and nature-based features for coastal resilience using a GIS-based ranking framework – an exportable approach - Hendricks, Jessica; Mason, Pamela; Herman, Julie; Hershner, Carl (Frontiers in Marine Science, 2023)
Increasing the preservation and creation of natural and nature-based features (NNBF), like wetlands, living shorelines, beaches, dunes and other natural features to improve community resilience in the face of increasing coastal flooding may be achieved by highlighting the locally relevant benefits that these features can provide. Here we present a novel application of the least-cost geospatial modeling approach to generate inundation pathways that highlight landscape connections between NNBF and vulnerable infrastructure. Inundation pathways are then used to inform a ranking framework that assesses NNBF based on their provision of benefits and services to vulnerable infrastructure and for the broader community including 1) the flooding mitigation potential of NNBF, 2) the relative impact of those NNBF on local infrastructure, and 3) co-benefits for the broader community linked to incentive programs like nutrient reduction crediting and the Federal Emergency Management Agency’s Community Rating System. Inundation pathways are also used to identify locations lacking in benefits from NNBF as target areas for NNBF restoration or creation. This approach, applied here for coastal Virginia, with project outputs available via an interactive map viewer1, can be customized for application in any community to identify high-priority NNBF that are particularly beneficial for preservation and to identify target areas for new or restored features.